2004
DOI: 10.1007/s10048-004-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

NR2A and NR2B receptor gene variations modify age at onset in Huntington disease

Abstract: N -Methyl-d-aspartate (NMDA) receptor-mediated excitotoxicity has been proposed to play a role in the pathogenesis of Huntington disease (HD), an autosomal dominantly inherited disorder associated with defined expansions in a stretch of perfect CAG repeats in the 5' part of the IT15 gene. The number of CAG repeat units is highly predictive for the age at onset (AO) in HD. However, AO is only modestly correlated with repeat length when the HD expansion range is in the high 30s or low 40s. Therefore, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 14 publications
3
67
0
5
Order By: Relevance
“…From the latter standpoint, it has been shown that the presence of the NR2A and NR2B subunits, primarily expressed in the striatum, may influence the age of onset of Huntington's chorea (Arning et al, 2005). Another study has suggested a link between the NR2A level and the symptomatic progression of this disease (Ali and Levine, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…From the latter standpoint, it has been shown that the presence of the NR2A and NR2B subunits, primarily expressed in the striatum, may influence the age of onset of Huntington's chorea (Arning et al, 2005). Another study has suggested a link between the NR2A level and the symptomatic progression of this disease (Ali and Levine, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The relative content of NR2A subunits of NMDA receptors (NMDARs) plays a key role in motor skill performance (25,26) and is genetically associated with HD age of onset (20)(21)(22). Therefore, we tested whether NR2A subunit trafficking and surface expression are altered in symptomatic zQ175 mice.…”
Section: Resultsmentioning
confidence: 99%
“…symptoms in HD patients (20)(21)(22), and the function of NR2 subunits is also significantly reduced in the striatum from HD brains compared with normal brains, as assessed by glutamate bindings (23,24). Furthermore, NR2A and NR2B subunits play distinct roles in striatum-mediated motor functions.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to a search for genetic modiiers and environmental factors that inluence the AO. Diverse modiier candidate loci have been suggested to be associated with AO in HD such as GRIN, TP53, hCAD, UCHL1, BDNF, ASK1, and MTHFR [14,17,[23][24][25][26][27][28][29][30][31][32]. However, many reports from diferent research groups have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…There is a signiicant inverse correlation between the AO and the CAG repeat length [11,12]. However, the number of the CAG repeats does not allow an accurate prediction of AO, only 30-70% of the variance in AO can be explained by the repeat size alone [13][14][15][16][17][18][19][20]. The AO varies signiicantly among individuals with the same CAG size, and even monozygotic HD twins may show phenotypic discordance for the disease [21,22].…”
Section: Introductionmentioning
confidence: 99%